2019
DOI: 10.1101/595173
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mycobacterium tuberculosis cording in the cytosol of live lymphatic endothelial cells

Abstract: 18The ability of Mycobacterium tuberculosis to form serpentine cords is intrinsically related to 19 its virulence, but specifically how M. tuberculosis cording contributes to pathogenesis 20 remains obscure. We show that several M. tuberculosis clinical isolates form intracellular 21 cords in primary human lymphatic endothelial cells (hLEC) in vitro and also in the lymph 22 nodes of patients with tuberculosis. We identified via RNA-seq a transcriptional programme 23 in hLEC that activates cellular pro-survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The difference in antibiotic susceptibility between both phenotypes estimated by mathematical approximation disappeared after the MIC values were transposed to their ISO standards indicating that it was a marginal difference and should be interpreted with caution and more experimental evidence including larger range of tested concentrations would be needed to confirm that. It has been shown that cords consist of bacterial cells with smaller volume than cells in non-cording aggregates which can indicate more active replication within the cord (8). In line with this, the total area of cording bacteria was increasing much faster from the initial time point than the planktonic, which we have also shown previously (5).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The difference in antibiotic susceptibility between both phenotypes estimated by mathematical approximation disappeared after the MIC values were transposed to their ISO standards indicating that it was a marginal difference and should be interpreted with caution and more experimental evidence including larger range of tested concentrations would be needed to confirm that. It has been shown that cords consist of bacterial cells with smaller volume than cells in non-cording aggregates which can indicate more active replication within the cord (8). In line with this, the total area of cording bacteria was increasing much faster from the initial time point than the planktonic, which we have also shown previously (5).…”
Section: Discussionsupporting
confidence: 88%
“…Recently, the cording phenotype has been shown to cause extensive immunopathological changes associated with active TB in C3HeB/FeJ mice (6). Mtb cords were also identified inside human alveolar macrophages obtained from patients with active TB (7) and lymphatic endothelial cells isolated from patients with extrapulmonary TB (8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we chose a specific edge threshold guided by domain expertise and supported by relevant literature [ 67 ], [ 68 ], mainly focusing on the cord of mycobacterium and the macrophage nucleus radius. This decision was made based on the recommendations of Dr. Gillian Beamer, a veterinary pathologist and a research scientist specializing in tuberculosis.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that AFBs can interact with other AFBs within 150 μ m [ 67 ]. It is equivalent to 615 pixels in the magnification of this study.…”
Section: Methodsmentioning
confidence: 99%